2021
DOI: 10.2147/ijn.s303816
|View full text |Cite
|
Sign up to set email alerts
|

Study of Uptake Mechanisms of Halloysite Nanotubes in Different Cell Lines

Abstract: Halloysite nanotubes (HNTs) are a natural aluminosilicate clay with a chemical formula of Al 2 Si 2 O 5 (OH) 4 ×nH 2 O and a hollow tubular structure. Due to their peculiar structure, HNTs can play an important role as a drug carrier system. Currently, the mechanism by which HNTs are internalized into living cells, and what is the transport pathway, is still unclear. Therefore, this study aimed at establishing the in vitro mechanism by which halloysite nanotubes could be internalized, using phagocytic and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In addition, cells treated with chlorpromazine (an inhibitor of clathrin-mediated endocytosis), colchicine (an inhibitor of microtubule formation and macropinocytosis), and brefeldin A (an inhibitor of protein transport from the endoplasmic reticulum to the Golgi apparatus) showed a 36%, 39%, and 31% decrease in cellular uptake, respectively as reflected in the decrease in fluorescence signals. The cellular uptake of rhApoE/Cou-6/Aβ-CN-PMs was partially dependent on clathrin-mediated endocytosis, macropinocytosis, and the Golgi apparatus [ 41 43 ]. Sodium azide (NaN 3 ) is used to inhibit energy-dependent endocytosis by disrupting ATP production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cells treated with chlorpromazine (an inhibitor of clathrin-mediated endocytosis), colchicine (an inhibitor of microtubule formation and macropinocytosis), and brefeldin A (an inhibitor of protein transport from the endoplasmic reticulum to the Golgi apparatus) showed a 36%, 39%, and 31% decrease in cellular uptake, respectively as reflected in the decrease in fluorescence signals. The cellular uptake of rhApoE/Cou-6/Aβ-CN-PMs was partially dependent on clathrin-mediated endocytosis, macropinocytosis, and the Golgi apparatus [ 41 43 ]. Sodium azide (NaN 3 ) is used to inhibit energy-dependent endocytosis by disrupting ATP production.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that HNTs do not exhibit a significant haemolytic effect [ 88 ]. It has also been seen that HUVECs (human umbilical vein endothelial cells) and MCF-7 (human breast cancer) cells show high cell viability after being treated with different concentrations of HNTs for 24 h. For both cell lines, vitality remains above 85% even when the concentration of HNTs reaches up to 200 mg/mL.…”
Section: Halloysite Biocompatibilitymentioning
confidence: 99%
“… In vitro hemocompatibility assay of ( A ) raw HNT and ( B ) HNT/CURBO after incubation at 37 °C for 12 h. The positive control was in ultrapure water (100% lysis), and negative control was in PBS 1× (0% lysis). International Journal of NanoMedicine 2021:16 4755–4768 Originally published by and used with permission from Dove Medical Press Ltd [ 88 ]. …”
Section: Figurementioning
confidence: 99%
“…Regarding biocompatibility, recent studies have clearly demonstrated that pristine HNTs can easily penetrate the cell membrane and accumulate in the perinuclear areas without causing significant toxic effects. [24][25][26][27] All these appealing features of HNTs encouraged us to explore the potential of these nanotubes for designing a new smart nanocarrier with temperature-mediated release behavior. For this purpose, PNIPAM brushes were grown on the surface of HNTs using a surface-initiated activator regenerated by electron transfer in atom transfer radical polymerization (ARGET-ATRP).…”
Section: Introductionmentioning
confidence: 99%